PENGGUNAAN MEDIA PEMBELAJARAN SEDOTAN (DRINGKING STRAWS) DAN KANTONG DALAM MENINGKATKAN HASIL BELAJAR - An Nisa, Winni (Jurnal Penalaran dan Riset Matematika, 2023)
In learning mathematics, teachers only use book media and lecture methods, namely the teacher explains then students take notes. Especially in the numerical material, the teacher has not used the maximum learning media, therefore making students unable to understand the numerical material as a whole. As for this research, formulating the problem "The use of media straws (Drinking Strawss) and number bags in improving mathematics learning outcomes in class IV UPTD SDN 104 Inpres Makkaraeng This type of research is a class action research (PTK). This class action research is an observation of learning activities in the form of an action, which is deliberately raised and occurs in a class together. The action is given by the teacher or with direction from the teacher carried out by students. During the implementation of cycle 2, observations on students were carried out using a previously prepared format or student observation sheet, which aims to determine the extent to which the Numbers Bag media can improve student learning outcomes. Reflection, At this stage of cycle 1, there were several students whose scores were still below the KKM, because students also did not fully understand the media directly exemplified by the researcher. In cycle 2, student learning outcomes have improved better than in cycle 1. This can be seen from the results of the post-test given as a benchmark for assessing the final results of the application of the number bag media on the learning outcomes of grade IV students. It is concluded that the use of straw media in mathematics learning can improve the learning outcomes of grade IV students of UPT SDN No.141 Makkaraeng. This is evidenced by the activities of grade IV students in learning mathematics using straw media have increased. This can be seen from the percentage of student activity in cycle I of 18,5% and increased by 62% to 81% in cycle II (3) the learning outcomes of grade IV students at UPT SDN No. 141 Inpres Makkaraeng on mathematics learning have increased from cycle I and cycle II. In cycle II, student learning outcomes have reached the success indicator.